2000
DOI: 10.1103/physrevb.61.7284
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic surface structure of liquid alkali metals

Abstract: We report an x-ray scattering study of the microscopic structure of the surface of a liquid alkali metal. The bulk liquid structure factor of the eutectic K 67 Na 33 alloy is characteristic of an ideal mixture, and so shares the properties of an elemental liquid alkali metal. Analysis of off-specular diffuse scattering and specular x-ray reflectivity shows that the surface roughness of the K-Na alloy follows simple capillary wave behavior with a surface structure factor indicative of surface-induced layering. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 19 publications
0
42
0
Order By: Relevance
“…Mv, 64.70.Fx, 71.15.Pd X-ray reflectivity measurements on the surface of liquid metals and alloys, along with other techniques like diffuse scattering or grazing incidence diffraction, have shown the existence of layering in the ionic density profile. 1,2,3,4,5,6,7,8 Its origin is yet not clear and several reasons have been mooted. Rice and coworkers 9,10,11 have pointed that the reason for surface layering in metals is the interconnection between the ionic and electronic densities and that the abrupt decay of the electron density at the surface induces an effective wall against which the ions, behaving like hard-spheres, stack.…”
mentioning
confidence: 99%
“…Mv, 64.70.Fx, 71.15.Pd X-ray reflectivity measurements on the surface of liquid metals and alloys, along with other techniques like diffuse scattering or grazing incidence diffraction, have shown the existence of layering in the ionic density profile. 1,2,3,4,5,6,7,8 Its origin is yet not clear and several reasons have been mooted. Rice and coworkers 9,10,11 have pointed that the reason for surface layering in metals is the interconnection between the ionic and electronic densities and that the abrupt decay of the electron density at the surface induces an effective wall against which the ions, behaving like hard-spheres, stack.…”
mentioning
confidence: 99%
“…This behavior does not generally occur at free surfaces of liquid dielectrics -though it is well known that atomic layers form at the solid-liquid interfaces of both dielectric and metallic substances 38 due to geometrical confinement. Surface-induced layering at free liquid metal surfaces was predicted theoretically 7,8,9,10,16,17,18,37 , and subsequently confirmed experimentally 20,26,29,31,32,33,34,35,39,46,47 for various metals and alloys by x-ray reflectivity…”
Section: Introductionmentioning
confidence: 57%
“…Growth of materials with the same chemical composition but with different crystalline structures (for example polytypic and/or polymorphic modifications of SiC, grown on SiC or ZnS-on ZnS and etc. ), showed that in a liquid phase growth process a new polytypic or polymorphic modification arises very seldom [14,15]. With the aim to realize a parallel growth of two polytypic modifications of 4H-SiC and 6H-SiC on 6H-SiC, we have established that in the most experiments the layers reproduce the substrate's modification.…”
Section: Reasons For the Modelmentioning
confidence: 98%
“…• C (the monotectic temperature) between the Bi monolayer, situated on the surface, and Ga-rich bulk resides a 30 0 A thick Bi-rich wetting film [12][13][14][15]. In the present article a different point of view concerning the structure of the phase boundary region and the processes, carried out there, is presented.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation